Study physical properties of natural rubber filled seashell powder / Wahidah Shakira Abdullah - Abdullah, Wahidah Shakira (2010)
The main objectives of this project are to reutilize seashell on rubber compound to minimize the disposal problems and also for economic reason where the seashell powder is added into new rubber compound formulation to reduce the production cost. Seashell which is rich with the mineral of calcium carbonate is suitable choice as filler in order to replace calcium carbonate commercial function. The effect of addition of seashell on physical properties of new natural rubber compound formulations was investigated by using different loading of seashell that varies from 0, 20, 30, 40 and 50 pphr. The result indicate that the incorporation of seashell rubber compound reduce the cure time. The maximum tensile strength can be obtained at 20 pphr of seashell loading and when higher of seashell added, the tensile strength will be reducing significantly. The hardness increase slightly when seashell loading used. Instead, resilience will decrease slightly when the seashell loading added.